Euler-Lagrange CFD modelling of unconfined gas mixing in anaerobic digestion. (15th November 2015) - Dapelo, Davide; Alberini, Federico; Bridgeman, John
Abstract: A novel Euler-Lagrangian (EL) computational fluid dynamics (CFD) finite volume-based model to simulate the gas mixing of sludge for anaerobic digestion is developed and described. Fluid motion is driven by momentum transfer from bubbles to liquid. Model validation is undertaken by assessing the flow field in a labscale model with particle image velocimetry (PIV). Conclusions are drawn about the upscaling and applicability of the model to full-scale problems, and recommendations are given for optimum application. Highlights: A CFD model for gas mixing in anaerobic digestion is developed. We present the first Euler-Lagrange model for the scope. Motion arises by momentum transfer from bubbles to liquid phase. Lab-scale validation with PIV technique was carried out. The model reproduces well the experimental data.